Differential Expression of Remodeling Markers by Tissue Structure in Nasal Polyposis. Issue 3 (May 2013) - Callejas, Francisco de Borja; Picado, Cesar; Martínez-Antón, Asunción; Alobid, Isam; Pujols, Laura; Valero, Antonio; Roca-Ferrer, Jordi; Mullol, Joaquim
Background: Data on the expression and role of matrix metalloproteinases (MMPs) and their tissue inhibitors (tissue inhibitor of metalloproteinases [TIMPs]) in chronic rhinosinusitis with nasal polyps (CRSwNPs) are contradictory, partly because or the use of different techniques of tissue analysis. The aim of this study was to establish a qualitative/semiquantitative method of analysis on the expression of these remodeling markers in different tissue structures and eosinophils in both NPs and nasal mucosa (NM). Methods: NP tissues were obtained from patients undergoing endoscopic sinus surgery for severe CRSwNPs (n = 33) and NM tissues from patients undergoing nasal corrective surgery (n = 12). MMPs (MMP-1, MMP-2, MMP-7, and MMP-9) and TIMP type 1 (TIMP-1) expression were evaluated by immunohistochemistry in tissue structures (epithelium, glands, vessels, and extracellular matrix [ECM]) and eosinophils. Tissue eosinophilia was also analyzed in NP tissues. Results: MMPs and TIMP-1 expression were found in the epithelium, glands, vessels, and ECM (in both NM and NP) and in eosinophils (only in NP). Significant (p < 0.01) findings were observed in NP compared with NM: increase in MMP-1 in ECM; decrease in MMP-2 in glands, vessels, and epithelium; decrease in MMP-7 in all tissue structures; increase in MMP-9 in ECM and decrease in epithelium and glands; and no differences in TIMP-1. NP tissues showed a clear eosinophilic inflammation compared with NM (p < 0.01). Conclusion: These findings suggest that (1) metalloproteases (MMP-1, MMP-2, MMP-7, and MMP-9) may play an important role in the remodeling of NPs and/or in NP formation and (2) a differential analysis of tissue structures and inflammatory cells should be performed when studying remodeling marker expression and regulation in the upper airways.